2013
DOI: 10.5937/sjecr14-4388
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate modulations in overtraining syndrome

Abstract: Every sports training program includes a component of repetitive overloading, but with an inadequate recovery time, such overloading may produce undesired eff ects, such as chronic fatigue and a lack of performance improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Several studies have reported changes in vagal activity as the result of overreaching and overtraining, with depressions in vagal activity at rest being among the most observed [ 7 , 28 , 29 , 30 ]. It was hypothesized that the BB group may be more susceptible to overtraining due to the increases in resistance training and volume that occurs during the off-season phase, which may be reflected through HRV markers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported changes in vagal activity as the result of overreaching and overtraining, with depressions in vagal activity at rest being among the most observed [ 7 , 28 , 29 , 30 ]. It was hypothesized that the BB group may be more susceptible to overtraining due to the increases in resistance training and volume that occurs during the off-season phase, which may be reflected through HRV markers.…”
Section: Discussionmentioning
confidence: 99%